Bridge preventive maintenance based on life-cycle assessment - de León Escobedo, David; Torres Acosta, Andrés (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
A criterion for preventive maintenance scheduling (PMS) is proposed based on the history of previous damage occurrences, duration of repairs or maintenance, and the development of cost functions. The PMS method describes the performance of the bridge for the deterioration/damage events and maintenance actions during the bridge's service life. The time to failure and repair time are modeled s random variables. Sensitivity studies show that the maintenance cost by damage consequence, an indirect measure of the bridge importance, plays a significant role on the optimal maintenance period.